2001
DOI: 10.1159/000051789
|View full text |Cite
|
Sign up to set email alerts
|

Anetoderma in a Systemic Lupus erythematosus Patient with Anti-PCNA and Antiphospholipid Antibodies

Abstract: Anetoderma is a rare elastolytic disorder included within the group of cutaneous atrophies. Its pathogenesis is not yet clearly established, but immunological mechanisms could play an important role in dermal elastolysis. It has been associated with different autoantibodies and autoimmune disorders. We present a case of anetoderma in a systemic lupus erythematosus patient with anti-proliferating-cell-nuclear-antigen and antiphospholipid antibodies, highlighting the peculiarities of such an association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…23 Associated conditions. Secondary anetoderma has been associated with urticaria pigmentosa, 24 syphilis, 25 acne, 26 varicella, 27 Lyme disease, 28 leprosy, 29 HIV infection, 30,31 lymphoproliferative disorders, 32,33 Langerhans cell histiocytosis, 34 systemic lupus erythematosus, 14,35,36 primary hypothyroidism, 37 Graves disease, 38 Addison disease, 14 antiphospholipid syndrome, 39 Sjögren syndrome, 40 prurigo nodularis, 41 pilomatricoma, 42,43 application of leeches, 44 electrocardiographic lead placement, 45 hepatitis B vaccination, 46 chronic angular cheilitis, 47 congenital melanocytic nevi with hamartomatous features, 48 juvenile xanthogranuloma, 49 and generalized granuloma annulare. 50 Involvement of extracutaneous elastic tissue has not been reported.…”
Section: Anetodermamentioning
confidence: 99%
“…23 Associated conditions. Secondary anetoderma has been associated with urticaria pigmentosa, 24 syphilis, 25 acne, 26 varicella, 27 Lyme disease, 28 leprosy, 29 HIV infection, 30,31 lymphoproliferative disorders, 32,33 Langerhans cell histiocytosis, 34 systemic lupus erythematosus, 14,35,36 primary hypothyroidism, 37 Graves disease, 38 Addison disease, 14 antiphospholipid syndrome, 39 Sjögren syndrome, 40 prurigo nodularis, 41 pilomatricoma, 42,43 application of leeches, 44 electrocardiographic lead placement, 45 hepatitis B vaccination, 46 chronic angular cheilitis, 47 congenital melanocytic nevi with hamartomatous features, 48 juvenile xanthogranuloma, 49 and generalized granuloma annulare. 50 Involvement of extracutaneous elastic tissue has not been reported.…”
Section: Anetodermamentioning
confidence: 99%
“…Despite this fact, a definitive relationship between LE and anetoderma has not been proven. However, the association between anetoderma and APAs has been documented previously (5,6,11,12), as well as a relationship between LE and APAs (5,6,11,13,14). Stephansson & Niemi (11), reviewing a group of SLE patients with and without APAs, observed that 15% of those with positive APAs developed anetoderma, while none of those without these antibodies developed this skin condition.…”
Section: Discussionmentioning
confidence: 88%
“…Antiphospholipid antibodies have been reported to associate with several cutaneous diseases in which vascular abnormalities seem to play a major part. Recently, nonvascular, cutaneous diseases including melanoma and anetoderma have been reported in patients with antiphospholipid antibodies [6, 7, 8]. To our knowledge, these are the first reported cases of subcutaneous GP associated with antiphospholipid antibodies.…”
Section: Discussionmentioning
confidence: 96%